Existence and Stability of Almost Periodic Solution for a Stochastic Cellular Neural Network with External Perturbation - Hui Zhou; Zongfu Zhou; Wei Jiang (Abstract and Applied Analysis)
A class of stochastic cellular neural networks with external perturbation is investigated. By employing fixed points principle and some stochastic analysis techniques, we establish some sufficient conditions for existence and exponential stability of a quadratic mean almost periodic solution of the model. The new criteria not only improve some classical results but also are applied in real problems due to the changes of external input.